Design and Implementation of a Network Based Multi-Axis Motion Control System for Laboratory Studies - (:unkn) unknown (My University, 2020)
In this study, an open source network based three axis motion control system has been designed and implemented to be used within motion control courses at engineering and technical branches for applicational studies. This system has been developed by using open source code and suitable physical structure for engineering studies. This experimental set has been evaluated by 107 students in related courses which are electrical machines and servo systems. Students have conducted various experiments by using single, two and three axes respectively. These students have been subjected to a Learner Satisfaction Survey which focuses on cognitive, affective and psychomotor extend of experimental studies in the laboratory with the designed motion control system. It has been observed from the results of this survey that learner - centered approach with the experimental set contribute in learning process positively.